Inovasi Bisnis Keunggulan Baru pada Berkah Coffe Mak'ju (BCM) dengan Pendekatan Bisnis Model Kanvas dan Ten Types of Innovations - Indah Khoirun Nisa; Beni Dwi Komara (Universitas Batanghari Jambi, 2023)
Berkah Coffe Mak'ju is one of the coffee entrepreneurs in Sidayu District, Gresik Regency with the highest consumer interest in Sidayu District. This is shown by the turnover income of more than 65 million per year and this figure is higher than other coffee MSMEs in Sidayu District, Gresik Regency. However, the revenue is still not in accordance with the desired target. Therefore, new innovations are needed to be able to achieve the desired income target. This study aims to find out the innovations and tactics that have been implemented by competitors and Berkah Coffe Mak'ju, innovations and tactics recommended to increase turnover in the Berkah Coffe Mak'ju business and the Berkah Coffe Mak'ju canvass business model so that the business can be sustainable. This study uses descriptive qualitative methods on Mak'ju Coffe Blessings in Ngawen Village, Sidayu District, Gresik Regency with data collection techniques in the form of observation, interviews, and documentation studies. The data was taken from one business owner, one supplier and three competitors, namely Cakri and Lajiem from Gresik city and Mahkota Raja from Sidorjo city. The results of the study show that the business innovation that has been used by Berkah Coffe Mak'ju to get high turnover is by using Cost Leadership, Focus, and Inderect Distribution tactics and competitors Cak Ri, Lajiem, and Mahkota Raja have similarities in using tactics namely, Focus tactics , Customization, and Diversification, and each competitor has different tactics. New innovations that are right to use Berkah Coffe Mak'ju use Cost Leadership, Premium, Customization, Guarantee, and Diversification tactics. The results of other studies also found a new business model canvas that is suitable to run on Berkah Coffe Mak'ju.